Wnt/ β-catenin and CTNNB1 gene mutation in hepatocellular carcinoma, a case study in Egyptian patients - Ramy A. Abdelsalam; Ibrahim M. El-Shawaf; Azza Abdel-Aziz; Tarek A. Bismar; Shaimaa M. Yussif (Surgical and Experimental Pathology)
Abstract Background Wnt/β-catenin pathway has an important role in hepatocarcinogenesis. It has been involved in progression, growth, epithelial mesenchymal transition and metastasis of hepatocellular carcinoma (HCC). This pathway may represent a potential target for evolving treatment strategies. β-catenin gene (CTNNB1) has been identified as an important oncogene involved in hepatocarcinogenesis in previous trials to understand the pathogenesis of HCC. This study aimed to spot light on the role of Wnt/ β-Catenin and CTNNB1 gene mutation in HCC development and its relation with different clinicopathological features. Patients and methods This study was conducted on 121 HCC cases that were obtained from liver explants from pathology laboratory at Mansoura Gastroenterology center retrospectively in the period between 2006-2017. Tissue Microarray (TMAs) were prepared. β-Catenin and Wnt immunohistochemical (IHC) staining was performed on these blocks. Detection and scoring of CTNNB1 gene mutation were done by Chromogenic In Situ Hybridization (CISH). The relation between aberrant β-Catenin, Wnt2 IHC staining and CTNNB1 mRNA expression and different clinicopathological characteristics was studied. Results A significant association was detected between aberrent β-catenin IHC staining and larger tumor size (p = 0.011), multiple tumor nodules (p = 0.021), higher stages of the tumor (p = 0.03) and with presence of lymphovascular emboli (LVE) (p = 0.034). However, no significant association was detected with tumor site, presence of lymph node spread, distant metastasis, tumor necrosis, local recurrence and alpha-fetoprotein level. No significant association was seen between Wnt2 IHC staining with either tumor site, tumor size, number of tumor nodules, presence of LVE, tumor necrosis, tumor grade, TNM stage or presence of local recurrence. A significant association was seen between CTNNB1 mRNA expression and larger tumor size (> 5 cm) (p = 0.041), higher tumor stages (Stages III and IV) (p = 0.005) and presence of distant metastasis (p = 0.008).). No significant association between CTNNB1 mRNA expression and LVE, tumor necrosis, tumor grade or occurrance of local recurrence. Conclusion Aberrant β-catenin IHC staining and CTNNB1 gene mutation in HCC correlate significantly with tumor size, number of tumor nodules, tumor stage and presence of LVE. All of these items confer poor prognosis in HCC. A highly significant correlation was detected between CTNNB1 gene mutation and aberrant β-catenin expression in HCC cases.